Nanobioarchitectures based on chlorophyll photopigment, artificial lipid bilayers and carbon nanotubes - Barbinta-Patrascu, Marcela Elisabeta; Iordache, Stefan Marian; Iordache, Ana Maria; Badea, Nicoleta; Ungureanu, Camelia (Beilstein Journal of Nanotechnology, 2014)
In the last decade, building biohybrid materials has gained considerable interest in the field of nanotechnology. This paper describes an original design for bionanoarchitectures with interesting properties and potential bioapplications. Multilamellar lipid vesicles (obtained by hydration of a dipalmitoyl phosphatidylcholine thin film) with and without cholesterol were labelled with a natural photopigment (chlorophyll a), which functioned as a sensor to detect modifications in the artificial lipid bilayers. These biomimetic membranes were used to build non-covalent structures with single-walled carbon nanotubes. Different biophysical methods were employed to characterize these biohybrids such as: UV–vis absorption and emission spectroscopy, zeta potential measurements, AFM and chemiluminescence techniques. The designed, carbon-based biohybrids exhibited good physical stability, good antioxidant and antimicrobial properties, and could be used as biocoating materials. As compared to the cholesterol-free samples, the cholesterol-containing hybrid structures demonstrated better stability (i.e., their zeta potential reached the value of −36.4 mV), more pronounced oxygen radical scavenging ability (affording an antioxidant activity of 73.25%) and enhanced biocidal ability, offering inhibition zones of 12.4, 11.3 and 10.2 mm in diameter, against Escherichia coli, Staphylococcus aureus and Enterococcus faecalis, respectively.
Keywords: antibacterial activity; antioxidant properties; artificial lipid bilayers; carbon nanotubes; chlorophyll

(untitled) - Sundberg, P.; Karppinen, M. (Beilstein J. Nanotechnol., 2014)

(untitled) - Ruiz, A.; Suárez, M.; Martin, N.; Albericio, F.; Rodríguez, H. (Beilstein J. Nanotechnol., 2014)

Bio-inorganic Hybrid Nanomaterials: Strategies, Syntheses, Characterization and Applications - Ruiz-Hitzky, E.; Darder, M.; Aranda, P. (An Introduction to Bio-nanohybrid Materials, 2008)

(untitled) - Barbinta Patrascu, M. E.; Ungureanu, C.; Iordache, S. M.; Bunghez, I. R.; Badea, N.; Rau, I. (J. Mater. Chem. B, 2014)

(untitled) - Barbinta-Patrascu, M. E.; Ungureanu, C.; Iordache, S. M.; Iordache, A. M.; Bunghez, I.-R.; Ghiurea, M.; Badea, N.; Fierascu, R.-C.; Stamatin, I. (Mater. Sci. Eng., C, 2014)

(untitled) - Barbinta-Patrascu, M. E.; Bunghez, I.-R.; Iordache, S. M.; Badea, N.; Fierascu, R.-C.; Ion, R. M. (J. Nanosci. Nanotechnol., 2013)

(untitled) - Mashaghi, S.; Jadidi, T.; Koenderink, G.; Mashaghi, A. (Int. J. Mol. Sci., 2013)

(untitled) - Rogers-Nieman, G. M.; Dinu, C. Z. (Wiley Interdiscip. Rev.: Nanomed. Nanobiotechnol., 2014)

Carbon Nanotubes and Related Structures. Synthesis, Characterization, Functionalization, and Applications - Guldi, D. M.; Martín, N. (Wiley-VCH, 2010)

(untitled) - He, H.; Pham-Huy, L. A.; Dramou, P.; Xiao, D.; Zuo, P.; Pham-Huy, C. (BioMed Res. Int., 2013)

(untitled) - Firme, C. P., III; Bandaru, P. R. (Nanomedicine, 2010)

(untitled) - Kam, N. W. S.; Jessop, T. C.; Wender, P. A.; Dai, H. (J. Am. Chem. Soc., 2004)

(untitled) - Villa, C. H.; Dao, T.; Ahearn, I.; Fehrenbacher, N.; Casey, E.; Rey, D. A.; Korontsvit, T.; Zakhaleva, V.; Batt, C. A.; Philips, M. R.; Scheinberg, D. A. (ACS Nano, 2011)

The Delivery of Nanoparticles - Kolosnjaj-Tabi, J.; Szwarc, H.; Moussa, F. (In vivo Toxicity Studies of Pristine Carbon Nanotubes: A Review, 2012)

(untitled) - Yang, S.-T.; Luo, J.; Zhou, Q.; Wang, H. (Theranostics, 2012)

(untitled) - Lim, J.-H.; Kim, S.-H.; Shin, I.-S.; Park, N.-H.; Moon, C.; Kang, S.-S.; Kim, S.-H.; Park, S.-C.; Kim, J.-C. (Birth Defects Res., Part B, 2011)

(untitled) - Kolosnjaj-Tabi, J.; Hartman, K. B.; Boudjemaa, S.; Ananta, J. S.; Morgant, G.; Szwarc, H.; Wilson, L. J.; Moussa, F. (ACS Nano, 2010)

(untitled) - Singh, G. P. B.; Baburao, C.; Pispati, V.; Pathipati, H.; Muthy, N.; Prassana, S. R. V.; Rathode, B. G. (Int. J. Res. Pharm. Chem., 2012)

(untitled) - Bianco, A.; Kostarelos, K.; Partidos, C. D.; Prato, M. (Chem. Commun., 2005)

(untitled) - Ghafari, P.; St-Denis, C. H.; Power, M. E.; Jin, X.; Tsou, V.; Mandal, H. S. (Nat. Nanotechnol., 2008)

(untitled) - Kagan, V. E.; Konduru, N. V.; Feng, W.; Allen, B. L.; Conroy, J.; Volkov, Y.; Vlasova, I. I.; Belikova, N. A.; Yanamala, N.; Kapralov, A.; Tyurina, Y. Y.; Shi, J.; et al. (Nat. Nanotechnol., 2010)

Liposomes: A practical approach - New, R. R. C. (IRL press, 1990)

The Chlorophylls - Strain, H. H.; Svec, W. A. (Extraction, separation, estimation, and isolation of the chlorophylls, 1966)

(untitled) - Hsu, C.-Y.; Chao, P.-Y.; Hu, S.-P.; Yang, C.-M. (Food Nutr. Sci., 2013)

(untitled) - Lanfer-Marquez, U. M.; Barros, R. M. C.; Sinnecker, P. (Food Res. Int., 2005)

Topics in Fluorescence Spectroscopy - Lakowicz, J. R. (Kluwer Academic Publishers, 2002)

(untitled) - Merényi, G.; Lind, J.; Eriksen, T. E. (J. Biolumin. Chemilumin., 1990)

(untitled) - Lind, J.; Merenyi, G.; Eriksen, T. E. (J. Am. Chem. Soc., 1983)

(untitled) - Lacatusu, I.; Badea, N.; Oprea, O.; Bojin, D.; Meghea, A. (J. Nanopart. Res., 2012)

(untitled) - Akhtar, S.; Sarker, M. R.; Hossain, A. (Crit. Rev. Microbiol., 2014)

(untitled) - Toval, F.; Köhler, C.-D.; Vogel, U.; Wagenlehner, F.; Mellmann, A.; Fruth, A.; Schmidt, M. A.; Karch, H.; Bielaszewska, M.; Dobrindt, U. (J. Clin. Microbiol., 2014)

(untitled) - Megged, O. (Pediatr. Nephrol., 2014)

(untitled) - Zipfel, P. F.; Skerka, C. (Int. J. Med. Microbiol., 2014)

(untitled) - Horsley, H.; Malone-Lee, J.; Holland, D.; Tuz, M.; Hibbert, A.; Kelsey, M.; Kupelian, A.; Rohn, J. L. (PLoS One, 2013)

(untitled) - Siddiqui, S. H.; Awan, K. H.; Javed, F. (Photodiagn. Photodyn. Ther., 2013)

(untitled) - Ansari, M. A.; Khan, H. M.; Khan, A. A.; Malik, A.; Sultan, A.; Shahid, M.; Shujatullah, F.; Azam, A. (Biol. Med., 2011)

Manual of clinical microbiology - Jorgensen, J. H.; Turnidge, J. D. (Susceptibility test methods: dilution and disk diffusion methods, 2007)

(untitled) - Liu, Y.-S.; Wen, C.-F.; Yang, Y.-M. (Sci. Adv. Mater., 2014)

(untitled) - Mishra, P. R.; Al Shaal, L.; Müller, R. H.; Keck, C. M. (Int. J. Pharm., 2009)

(untitled) - Jacobs, C.; Müller, R. H. (Pharm. Res., 2002)

(untitled) - Shameli, K.; Bin Ahmad, M.; Jazayeri, S. D.; Shabanzadeh, P.; Jahangirian, H.; Mahdavi, M.; Abdullahi, Y. (Int. J. Mol. Sci., 2012)

(untitled) - Galano, A. (Nanoscale, 2010)

(untitled) - Galano, A. (J. Phys. Chem. C, 2008)

(untitled) - Fenoglio, I.; Tomatis, M.; Lison, D.; Muller, J.; Fonseca, A.; Nagy, J. B.; Fubini, B. (Free Radical Biol. Med., 2006)

(untitled) - Watts, P. C. P.; Fearon, P. K.; Hsu, W. K.; Billingham, N. C.; Kroto, H. W.; Walton, D. R. M. (J. Mater. Chem., 2003)

(untitled) - Barbinta Patrascu, M. E.; Cojocariu, A.; Tugulea, L.; Badea, N. M.; Lacatusu, I.; Meghea, A. (J. Optoelectron. Adv. Mater., 2011)

(untitled) - Dong, X.; Tang, Y.; Lilly, M.; Aferchich, K.; Yang, L. (Nano LIFE, 2012)

(untitled) - Simmons, T. J.; Lee, S.-H.; Park, T.-J.; Hashim, D. P.; Ajayan, P. M.; Linhardt, R. J. (Carbon, 2009)

(untitled) - Kang, S.; Pinault, M.; Pfefferle, L. D.; Elimelech, M. (Langmuir, 2007)